PENGARUH FAKTOR SOSIAL EKONOMI RUMAH TANGGA TERHADAP KONSUMSI PRODUK PETERNAKAN DI KECAMATAN KASIHAN KABUPATEN BANTUL (JASEP, 2015)
The research was aimed to analyze the household consumption to livestock products in urban and rural areas in Kasihan, analyze household expenditures for egg products and other livestock products in Kasihan, and analyze the social and economic factors influence household consumption of livestock products in Kasihan. Selection of research location used purposive sampling method. This research was conducted by interviewing the housewife as the primary data and Bantul in figures in 2013 and Kasihan in number in 2013 as the secondary data. The sampling technique was used proportionate stratified random sampling. The method of analysis was based on cross-tabulation (crosstab) and regression analysis. The results of the research shows that the level of household consumption for livestock products is higher in urban areas than in rural areas. The level of household expenditures highest for livestock products was chicken. Social and economic factors influence the household consumption of chicken meat (r = 0.244), the consumption of milk (r = 0.982), and the consumption of chicken eggs (r = 0.244). Factors which affect the consumption of chicken meat was the price of chicken meat (α = 0.05). Factors which affect the consumption of milk is the number of family members (α = 0.05) and the price of milk (α = 0.01). Factors which affect the consumption of chicken eggs was member of the family income and the price of fish (α = 0.05). The strategy needs to be done to consumption of livestock products was planning diversification of consumption and consumption of livestock products.